Diversity, extinction risk and conservation of Malaysian fishes - Chong, V.C.; Lee, P.K.Y.; Lau, C.M. (Blackwell Publishing, 2010)
A total of 1951 species of freshwater and marine fishes belonging to 704 genera and 186 families are recorded in Malaysia. Almost half (48%) are currently threatened to some degree, while nearly one third (27%) mostly from the marine and coral habitats require urgent scientific studies to evaluate their status. Freshwater habitats encompass the highest percentage of threatened fish species (87%) followed by estuarine habitats (66%). Of the 32 species of highly threatened (HT) species, 16 are freshwater and 16 are largely marine-euryhaline species. Fish extinctions in Malaysia are confined to two freshwater species, but both freshwater and marine species are being increasingly threatened by largely habitat loss or modification (76%), overfishing (27%) and by-catch (23%). The most important threat to freshwater fishes is habitat modification and overfishing, while 35 species are threatened due to their endemism. Brackish-water, euryhaline and marine fishes are threatened mainly by overfishing, by-catch and habitat modification. Sedimentation (pollution) additionally threatens coral-reef fishes. The study provides recommendations to governments, fish managers, scientists and stakeholders to address the increasing and unabated extinction risks faced by the Malaysian fish fauna.